AGRICULTURAL LAND CONVERSION: DETERMINANTS AND IMPACT FOR FOOD SUFFICIENCY IN SLEMAN REGENCY - Harini, Rika ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research was conducted in Sleman Regency with 3 study area based on the extent of agricultural land conversion. The purpose of this research is to examine the determinants of agricultural conversion internally and externally, as well as the impact on the availability of food, epecially rice. The research was conducted by survey method and statistical analysis regression Ordinary Least Square. The resultsof this research showed that the internal factors which significantly affect land conversion is the price of land and land location in all areas of study. External factors have significantly positive are variable population, land conversion rules and land location, while the variable GDP in the agricultural sector negatively. Availability of rice in Sleman Regenct zone 1 indicates the region from 1983 to 2025 for the population minus the rice sufficiency. In zone 2 region between 1983 and 2005 but it is still a surplus between 2006 and 2025 minus. In the area of zone 3 is projected through 2025 the availability of rice is sufficient